Condition based gearbox maintenance for industry 4.0 - Dwarakesh, Chandrasekar (Nanyang Technological University, 2020)
Gearboxes continue to play a critical role in many industrial applications with various operational loads and environmental conditions. Maintenance is a crucial aspect of gearbox installations. Thus, a well-planned gearbox maintenance strategy reduces unplanned downtimes due to breakdown and ensures continuous operation during its service life. One such maintenance strategy is condition-based maintenance, which is supported by wireless sensor networks and other technological pillars which form the industry 4.0 paradigm. This report firstly covers some of the engineering concepts in gearbox tribology and vibration, which prove to be beneficial in identifying incipient faults within the gearbox. In addition, this report also presents an overview of the main subsystems in a wireless vibration sensor node, which is found in many wireless sensor networks. Finally, an experiment was conducted with a wireless vibration sensor node to study the vibration response of a gear box under various operating conditions.